2020
DOI: 10.21203/rs.3.rs-27746/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in clinicopathological features and molecular phenotype of breast carcinoma between patients younger than 40 years and those who are older: A study from Pakistan

Abstract: Background The debate whether breast cancer in women under 40 years of age is distinct from breast cancer in women above 40 is still inconclusive with various published studies providing conflicting evidence. The majority of studies however suggest that breast cancer in younger women (< 40) is more aggressive with worse clinicopathological features. However, the issue is by no means settled and a number of studies are still going on. Our objective was to analyze different clinicopathological variables and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The findings are slightly less than a study which showed 71% cases had ER and PR positive tumors. 15 The baseline characteristics of present study sample also ascertain that grade 2 and stage 3 breast cancer are found commonly. The findings are also in concurrence with other studies.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The findings are slightly less than a study which showed 71% cases had ER and PR positive tumors. 15 The baseline characteristics of present study sample also ascertain that grade 2 and stage 3 breast cancer are found commonly. The findings are also in concurrence with other studies.…”
Section: Discussionmentioning
confidence: 79%
“…The findings are also in concurrence with other studies. [13][14][15] In the current study, majority of the patients presented with lymph node involvement. Saleh et al reported that in 774 breast cancer patients, 35.5% had axillary lymph node involvement at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 92%